Evaluation the Efficacy of ELISA IgG, IgM and IgA Tests for Diagnosis of Helicobacter pylori - Mohammed Shukri Saadi, Hogir; Yahya Saeed, Ali (Kurdistan Journal of Applied Research, 2018)
It has been well recognized throughout the world that Helicobacter pylori is the main cause of gastric ulcer and stomach carcinoma. Laboratory diagnosis of H. pylori infection is made by invasive and non-invasive methods. Invasive methods require endoscopy which is uncomfortable an unacceptable by the most patients. Therefore, non-invasive methods particularly serological tests are easier and comfortable for patients. A total of 86 patients with ages ranging from 18-77 years old (43 males and 43 females) who were referred to the Duhok Hepatology & Gastroenterology center/Azadi Teaching Hospital for endoscopic examination from June to October, 2013 were enrolled in the study. From each patient 5 ml of blood was collected under a septic condition and sera were separated for serology. Data from each participant were recorded in a special questionnaire form after consent agreed upon on ethical and scientific committee of the Azadi hospital. The efficacy of three different ELISA tests (IgG, IgM, IgA) was assessed taking culture as a gold standard method. pylori was found in 70.93%, 30.23% and 5.81% by ELISA IgG, IgA and IgM tests respectively. The highest percentage (70.93%) of H. pylori positive cases were found by ELISA IgG and the lowest percentage (5.81%) was recorded in ELISA IgM. The study found a significant relationship between age groups and H. pylori positive cases by ELISA IgG in which positive cases increased with the increase of ages.No statistical correlation was found between the sex, smoking status and residency of studied patients with H. pylori infection. A significant correlation was found between patients without endoscopic lesions and positive cases for H. pylori by ELISA IgG in which 75.67% of patients without endoscopic lesions were positive for anti-H. pylori antibodies compared to 41.66% in patients with endoscopic lesions.The efficacy of IgG, IgM and IgA tests was calculated compared with golden standard tests and ELISA IgG characterized by the highest values of sensitivity (75.75%), negative predictive value (36.00%) and accuracy (86.00%) but with lowest specificity (45.00%) and similar positive predictive value (81.96%) with IgM and IgA. The lowest sensitivity was 5.97% and accuracy 25.56% with ELISA Ig M. From the results of the present study we can conclude that among ELISA tests, anti-H. pylori IgG is a reliable serological test for the diagnosis of H. pylori infection.